Video-EEG telemetry: apparent manifestation of both epileptic and non-epileptic attacks causing potential diagnostic pitfalls. - Raymond, A.A.; Gilmore, W.V.; Scott, C.A.; Fish, D.R.; Smith, S.J. (1999)
Video-EEG telemetry is often used to support the diagnosis of non-epileptic seizures (NES). Although rare, some patients may have both epileptic seizures (ES) and NES. It is crucially important to identify such patients to avoid the hazards of inappropriate anticonvulsant withdrawal. To delineate the electroclinical characteristics and diagnostic problems in this group of patients, we studied the clinical, EEG and MRI features of 14 consecutive patients in whom separate attacks, considered to be both NES and ES were recorded using video-EEG telemetry. Only two patients were drug-reduced during the telemetry. Most patients had their first seizure (ES or NES) in childhood (median age 7 years; range: 6 months-24 years); 8/14 patients were female. Brain MRI was abnormal in 10/14 patients. Interictal EEG abnormalities were present in all patients; 13/14 had epileptiform and 1/14 only background abnormalities. Over 70 seizures were recorded in these 14 patients: in 12/14 patients, the first recorded seizure was a NES (p < 0.001), and 7 of these patients had at least one more NES before an ES was recorded. Only 3/14 patients had more than 5 NES before an ES was recorded. Recording a small number of apparently NES in an individual by no means precludes the possibility of additional epilepsy. Particular care should be taken, and multiple (> 5) seizure recording may be advisable, in patients with a young age of seizure onset, interictal EEG abnormalities, or a clear, potential aetiology for epilepsy.